Pengaruh Perencanaan Dan Kepemimpinan Terhadap Kinerja Karyawan Di Universitas SariPutra Indonesia Tomohon - Aotama, Reynaldo Christian (Universitas Sam Ratulangi, 2016)
The first important thing that indicate the effectiveness and efficiency from the organization is the well planing in implementation of the vision and mission that be appointed. The result of research found that planning (X1) and leadership (X2) are simoustinously has significantly effect to staff performance in University Sari Putra Tomohon Indonesia. is simoustinouslyhas significantly effect to staff performance in University Sari Putra Tomohon Indonesia. leadership is simoustinously has significantly effect to staff performance in University Sari Putra Tomohon Indonesia.Keywords: Planning, Leadership, Staff Performance